Analisis Gerakan Literasi Sekolah melalui Pojok Baca Siswa Kelas 4 SDN Pinang 1 - Fitri Maulida Awalina; Septy Nurfadhillah; Yeni Nuraeni (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study describes how the school literacy movement is through the reading corner of grade 4 students at SDN Pinang 1. The school literacy activity at SDN Pinang 1 is to get students used to reading for 15 minutes before and after learning and is carried out every day. The goal is that students get used to reading and can improve students in reading. Not only with the literacy movement to improve students' reading so that students in reading at SDN Pinang 1 also set up a corner which is expected to increase students' reading interest because students are closer to them. The technique used in this research is descriptive qualitative by using information collection methods in the form of observation, interviews, and documentation. Checking the validity of information using triangulation. Information is analyzed through the steps of gathering information, reducing information, presenting information, and drawing conclusions. Respondents in this research amounted to 14 people, namely the principal, the homeroom teacher for grade 4A, and 13 students in grade 4A. Based on the results of the research, the school literacy movement through the reading corner at SDN Pinang 1 ran efficiently even though it had been hampered by the pandemic.